Prediction on the Surface Phase Diagram and Growth Morphology of Nanocrystal Ruthenium Dioxide. Issue 11 (29th July 2014) - Xu, Canhui; Jiang, Yong; Yi, Danqing; Zhang, Haibin; Peng, Shuming; Liang, Jianhua; Rohrer, G.
<x xml:space="preserve">Abstract</x> Surface energy has an important role in controlling the exposed facets and growth morphology of nanocrystals. In this study, we employed first‐principle thermodynamic modeling and calculations to evaluate the substantial effects of environmental factors (temperature and oxygen partial pressure), on the surface structure, stability, and nanocrystal morphology of rutile‐type ruthenium dioxide (RuO2). Both stoichiometric and nonstoichiometric surfaces with ideal bulk terminations were assessed. The relative ordering of stoichiometric surface stabilities was predicted as (110) > (101) > (100) > (001). The sensitive environment dependence of nonstoichiometric surface stabilities was evaluated by calculating the surface phase diagram, and partially validated by comparing with available experimental observations. The predicted surface stabilities were further coupled with the Gibbs–Wulff construction of equilibrium crystal shape, to predict the morphological evolutions of RuO2 nanocrystals under practical growth conditions. A morphology‐controlled growth technique was finally suggested for designing and developing hierarchical nanostructures by intelligently adjusting the thermodynamic growth conditions.